Spinocerebellar ataxia type 14: refining clinicogenetic diagnosis in a rare adult‐onset disorder. Issue 4 (19th March 2021) - Schmitz‐Hübsch, Tanja; Lux, Silke; Bauer, Peter; Brandt, Alexander U.; Schlapakow, Elena; Greschus, Susanne; Scheel, Michael; Gärtner, Hanna; Kirlangic, Mehmet E.; Gras, Vincent; Timmann, Dagmar; Synofzik, Matthis; et al.
Abstract: Objectives: Genetic variant classification is a challenge in rare adult‐onset disorders as in SCA‐PRKCG (prior spinocerebellar ataxia type 14) with mostly private conventional mutations and nonspecific phenotype. We here propose a refined approach for clinicogenetic diagnosis by including protein modeling and provide for confirmed SCA‐PRKCG a comprehensive phenotype description from a German multi‐center cohort, including standardized 3D MR imaging. Methods: This cross‐sectional study prospectively obtained neurological, neuropsychological, and brain imaging data in 33 PRKCG variant carriers. Protein modeling was added as a classification criterion in variants of uncertain significance (VUS). Results: Our sample included 25 cases confirmed as SCA‐PRKCG (14 variants, thereof seven novel variants) and eight carriers of variants assigned as VUS (four variants) or benign/likely benign (two variants). Phenotype in SCA‐PRKCG included slowly progressive ataxia (onset at 4–50 years), preceded in some by early‐onset nonprogressive symptoms. Ataxia was often combined with action myoclonus, dystonia, or mild cognitive‐affective disturbance. Inspection of brain MRI revealed nonprogressive cerebellar atrophy. As a novel finding, a previously not described T2 hyperintense dentate nucleus was seen in all SCA‐PRKCG cases but in none of the controls. Interpretation: In this largest cohort to date, SCA‐PRKCG was characterized as a slowly progressive cerebellar syndrome with some clinical and imaging features suggestive of a developmental disorder. The observed non‐ataxia movement disorders and cognitive‐affective disturbance may well be attributed to cerebellar pathology. Protein modeling emerged as a valuable diagnostic tool for variant classification and the newly described T2 hyperintense dentate sign could serve as a supportive diagnostic marker of SCA‐PRKCG.